The Relationships among Self-Efficacy and Satisfaction of Nursing Students who Received Online Learning in COVID-19 Situations - Panya, Siriluck; Koomala, Soomisa; Khoyun, Siriorn (Journal of The Royal Thai Army Nurses, 2021)
This study was a descriptive correlation research. The study aimed at investigating the relationships between self-efficacy and satisfaction of nursing students who received online learning in COVID-19 situations. The sample consisted of 300 nursing students who online learning and register summer semester in academic year 2019 in government and private university in the north-eastern region of Thailand. The instruments used to collect data included a demographic characteristic questionnaire, Online learning self-efficacy scale and online learning satisfied questionnaire. Data were analyzed using frequency, percentage, mean and Spearmen’s rank correlation. The research findings revealed that self-efficacy was positively related to satisfaction of nursing students who received online learning with statistical significance (r = .666, p <.001). The study findings could be utilized to guidance for development self-efficacy promotion program in nursing students who received online learning.